Reverse Genetics Modification of Cytomegalovirus Antigenicity and Immunogenicity by CD8 T-Cell Epitope Deletion and Insertion - Lemmermann, Niels A. W. (Hindawi Publishing Corporation, 2011)
The advent of cloning herpesviral genomes as bacterial artificial chromosomes (BACs) has made herpesviruses accessible to bacterial genetics and has thus revolutionised their mutagenesis. This opened all possibilities of reverse genetics to ask scientific questions by introducing precisely accurate mutations into the viral genome for testing their influence on the phenotype under study or to create phenotypes of interest. Here, we report on our experience with using BAC technology for a designed modulation of viral antigenicity and immunogenicity with focus on the CD8 T-cell response. One approach is replacing an intrinsic antigenic peptide in a viral carrier protein with a foreign antigenic sequence, a strategy that we have termed “orthotopic peptide swap”. Another approach is the functional deletion of an antigenic peptide by point mutation of its C-terminal MHC class-I anchor residue. We discuss the concepts and summarize recently published major scientific results obtained with immunological mutants of murine cytomegalovirus.